Catalpol—a compound from Rehmannia glutinosa can improve hyperlipidemia by modulating gut microbiota and endogenous metabolic pathways - Pei, Xinfeng; Dong, Weichao; Yu, Yingying; Wang, Yinglei; Wang, Shaoping; Dai, Long (Frontiers in Microbiology, 2025)
IntroductionCatalpol, an iridoid glycoside derived from Rehmannia glutinosa, is widely recognized for its ability to reduce blood glucose levels. However, its potential therapeutic effects on hyperlipidemia (HL) have yet to be investigated.MethodsTo identify novel lipid-lowering effects of catalpol potentially exerted through the modulation of the gut microbiota and endogenous metabolic pathways, Sprague–Dawley (SD) rats were provided a high-fat diet (HFD) to induce an HL state. The lipid-lowering efficacy of catalpol was assessed using biochemical test kits. Subsequently, 16S rRNA gene sequencing was employed to analyze alterations in gut microbial composition in HL rats before and after catalpol treatment. Ultra-high-performance liquid chromatography coupled with Quadrupole Exactive Orbitrap mass spectrometry (UHPLC-Q Exactive Orbitrap MS) was used to detect and identify catalpol metabolites in plasma, urine, and feces. In addition, non-targeted metabolomics was conducted to characterize endogenous small-molecule metabolites.ResultsPharmacodynamic analysis demonstrated that catalpol markedly reduced lipid levels and inhibited hepatic lipid peroxidation. The 16S rRNA sequencing results showed that the consumption of an HFD led to a significant increase in the abundance of Firmicutes and a decrease in that of Bacteroidetes. Notably, catalpol treatment improved HL model rats’ overall gut microbiota structure. Non-targeted metabolomics revealed that the HFD significantly altered the abundance of 18 endogenous metabolites, changes that were reversed following catalpol administration. Spearman correlation analysis identified the genus Lactobacillus as a positive contributor to the anti-HL effect of catalpol. Furthermore, pteridine was identified as a potential biomarker associated with catalpol’s lipid-lowering activity.DiscussionCollectively, these findings demonstrate that catalpol alleviates HL by influencing gut microbiota composition and restoring plasma metabolic homeostasis.